2000
DOI: 10.1111/j.1502-3885.2000.tb01445.x
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent interaction between the Norwegian Channel Ice Stream and terrestrial‐based ice across southwest Norway

Abstract: The occurrence of till beds alternating with glaciomarine sediment spanning oxygen isotope stages 6 to 2, combined with morphological evidence, shows that the southwestern fringe of Norway was inundated by an ice stream flowing through the Norwegian Channel on at least four occasions, the last time being during the Late Weichselian maximum. All marine units are deglacial successions composed of muds with dropstones and diamictic intrabeds and a foraminiferal fauna characteristic of extreme glaciomarine environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 30 publications
0
45
0
Order By: Relevance
“…However, this would make the correlation with other sites on Jaeren difficult, as an interstadial with similar glaciomarine sediments has been confined to ca. 30-39 ka Larsen et al, 2000;Sejrup et al, 2000). Another possibility is that the Kalberg clay represents a hitherto unknown interstadial, but as discussed above we find this possibility unlikely.…”
Section: Correlation and Glacial Geological Implicationsmentioning
confidence: 62%
See 4 more Smart Citations
“…However, this would make the correlation with other sites on Jaeren difficult, as an interstadial with similar glaciomarine sediments has been confined to ca. 30-39 ka Larsen et al, 2000;Sejrup et al, 2000). Another possibility is that the Kalberg clay represents a hitherto unknown interstadial, but as discussed above we find this possibility unlikely.…”
Section: Correlation and Glacial Geological Implicationsmentioning
confidence: 62%
“…Feyling-Hanssen (1964) and Fugelli and Riis (1992) suggested they were tectonically uplifted glaciomarine sediments, whereas Andersen et al (1987Andersen et al ( , 1991 thought they were glaciomarine sediments deposited in periods of large glacio-isostatic depression owing to an ice sheet centred over central Norway. Sejrup et al (1998) suggested that glacio-isostatic loading by an ice stream in the Norwegian Channel could explain the high relative sea-levels during deposition of the marine clays on Jaeren, and this interpretation was later supported by Stalsberg et al (1999), Jonsdottir et al (1999) and Larsen et al (2000). Sejrup et al (1998) also suggest that the boundary between Høgjaeren and Lågjaeren is the easternmost boundary of the Norwegian Channel Ice Stream (NCIS).…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations